삼치 어육 가수분해물의 항산화 및 ACE 저해 활성 - 백다현(Dahyun Baek); 김인용(Inyong Kim); 정윤화(Yoonhwa Jeong) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구에서는 탈지 방법 및 가수분해 시간에 따른 삼치 어육의 항산화 및 ACE 저해 활성을 비교 분석하였다. 가수분해도는 탈지 후 익힘> 익힘 후 탈지> 생어육 탈지 순으로 높게 나타났으며, DPPH 라디칼 소거능은 5 mg/mL 농도에서 익힌 후 탈지 180분 가수분해물이 63.16%로 가장 높게 나타났다. 20 mg/mL에서는 탈지 후 익힘 180분 가수분해물이 89.47%로 가장 높았다. SOD 유사 활성은 가수분해 시간에 따라 활성이 증가하였으며 익힌 후 탈지 180분 가수분해물에서 가장 높은 활성을 나타내었다. 환원력의 경우 가수분해 전반부(30, 60분)에서 익힌 후 탈지 가수분해물이 가장 높은 활성을 나타내었으며, 2시간 후에는 생어육 탈지 가수분해물에서 높은 활성을 나타내었다. 아질산염 소거능은 pH 1.2에서 가장 높게 나타났으며, 그중 탈지 후 익힘 120분 가수분해물 50 mg/mL가 95.33%로 가장 높은 값을 나타내었다. ACE 저해 활성은 익힌 후 탈지 가수분해물이 높게 나타났으며, 탈지 후 익힘 처리군의 경우 가수분해도는 높게 나타났으나 익힌 후 탈지 처리군과 비교하여 동일 농도에서 낮은 활성을 나타내었다. 삼치 가수분해물의 경우 단백질가수분해 효소의 활성을 높이기 위해 탈지 과정이 필요하며, 탈지 과정을 가수분해 과정에 포함하고자 할 때 생어육에 비해 가열과정이 필요하다. 따라서 본 실험 결과를 검토하였을 때 탈지 후 가열과정을 거친 어육을 가수분해하는 것이 전반적으로 높은 활성을 나타내었다. This study examined the antioxidant and ACE inhibitory activities of Japanese Spanish mackerel hydrolysates treated with different defatting methods. The methods were divided into defatted raw meat, cooked meat after defatting, and defatted meat after cooking. These samples were hydrolyzed by Alcalase® for different hydrolysis times (30, 60, 120, and 180 min). The degree of hydrolysis increased with increasing hydrolysis time and followed by cooked meat after defatting raw meat, cooked meat after defatting, and defatted meat after cooking. The DPPH radical scavenging activity increased significantly with increasing hydrolysis time at 5 mg/mL and the highest points for each defatting method were 63.16% at 5 mg/mL of 180 min defatted meat after cooking and 89.47% at 20 mg/mL of 180 min in cooked meat after defatting. The hydrolysates of all defatting treatments increased significantly up to 120 min at 20 mg/mL and 50 mg/mL; the highest SOD-like activity was 58.90% at 50 mg/mL defatted meat after cooking for 180 min. The reducing power of the hydrolysates increased with increasing hydrolysis time after 60 min. Among all the results, 50 mg/mL cooked meat after defatting for 180 min produced the highest result. The nitrite scavenging activity of hydrolysates was higher at lower pH and was not active at pH 6, and the highest point was 95.33% of 50 mg/mL cooked meat after defatting for 120 min. The ACE inhibition activity, defatted meat after cooking was highest and the highest ACE inhibition activity was 90.20% at 18 min. KCI Citation Count: 4